A BALANCED APPROACH FOR FACILITATED, STEP LADDER LEARNING OF HUMAN PHYSIOLOGY - Alam, Tariq Mahmood (Pakistan Journal of Physiology, 2009)
Background: In Pakistan, the 1st Year and 2nd Year examinations are held separately, bifurcating each relevant subject in 2 almost water-tight compartments. The guiding principles by regulatory bodies explicitly spelt out that ‘Repetitive teaching of the same contents by different disciplines must be avoided, and the university faculty is free to decide the order in which to teach a subject’. Except few colleges taking marginal advantage of the above guidelines, most are still on board the same old boats. Currently, in 1st Year: General & Cell Physiology, Blood, Nerve & Muscle Physiology, GIT, CVS and Respiration; while in the 2nd Year, Body Fluids & Kidney, Nervous System, Special Senses, Endocrinology and Reproduction are covered. Disadvantages: 1) Maximum load of curriculum is shifted to 1st Year when the foliage students are already disturbed by numerous adverse factors. 2) The topics of Biological Membrane, Liver Functions, their tests & Jaundice in 1st Year and the Endocrinology and Acid/Base Balance in 2nd Year are being taught by Physiology & Biochemistry, generating duplication. A balanced approach is suggested to cover General & Cell Physiology, Blood, Nerve & Muscle Physiology, Respiration, Body Fluids & Kidney in 1st Year, while GIT, CVS, Nervous System, Special Senses, and Reproduction in the 2nd Year. Relevance will guide division of duplicated topics amongst Physiology and Biochemistry, avoiding unnecessary repetition. Advantages: 1) All prevailing disadvantages are eradicated. 2) All practicals in 2nd Year will be the clinical methods, facilitating clinical clerkship in 3rd year